Access to psoriasis treatment in Brazil and Chile: A cross-sectional multicentre Global Healthcare Study on Psoriasis. (19th January 2023) - Maul, Julia-Tatjana; Fröhlich, Fabienne; Maul, Lara Valeska; Stunnenberg, Rieka; Valenzuela, Fernando; De La Cruz, Claudia; Vera-Kellet, Cristián; Armijo, Daniela; Cesar, Wagner G; Carvalho, Andre; Didaskalu, Johannes Alexander; Graf, Nicole; et al.
Abstract: Background: Sufficient data on access to systemic treatment for patients with psoriasis living in Latin America (LA) including Brazil and Chile are lacking. Understanding the availability and limiting factors of access to treatments can help to improve patient care and decrease long-term healthcare costs. Objectives: In association with the Global Psoriasis Atlas, this cross-sectional survey study analysed the availability and insurance reimbursement of systemic treatments for adult patients with psoriasis in Brazil and Chile. Methods: A multicentre, cross-sectional Global Healthcare Study on Psoriasis was performed in Brazil and Chile in 2020. For each eligible adult patient with psoriasis, doctors and nurses completed a 48-item questionnaire about clinical aspects of psoriasis including the Psoriasis Area Severity Index (PASI), body surface area (BSA) score and the Dermatology Life Quality Index (DLQI), as well as the availability of systemic treatments and insurance reimbursement status. Between-country differences were compared with Wilcoxon rank sum tests for continuous variables, and a χ 2 -test or Fisher's exact test, where appropriate, for categorical variables. The median and interquartile range (IQR) was calculated for non-normal distributed data. Results: A total of 1424 patients with psoriasis from 43 centres [27 centres in Brazil ( n = 826) and 16 in Chile ( n = 598)], were included with a mean (SD) age of 49.1 (16.3) and 49.2 (15.1) years, respectively. Unstratified analyses revealed that patients with psoriasis in Chile had more severe disease than those in Brazil [PASI 11.6 vs. 8.4 ( P < 0.001) and BSA 14.7 vs. 12.0 ( P = 0.003), respectively]. For patients with moderate-to-severe psoriasis, defined as PASI and/or BSA ≥ 10, systemic nonbiologic drugs were available (81.2% in Brazil and 65.3% in Chile, P ≤ 0.001), but only 37.0% of patients in Brazil and 27.3% in Chile received biologics ( P = 0.01). Lack of availability and/or lack of insurance reimbursement for biologic drugs for patients with moderate-to-severe psoriasis was reported for 22.2% (50 of 225) in Brazil and 67.9% (148 of 218) in Chile ( P < 0.001). Patients with no access to biologic therapies due to lack of availability/insurance reimbursement had a median PASI of 9.15 (IQR 3.00–14.25) in Brazil and 12.0 (IQR 5.00–19.00) in Chile ( P = 0.007), as well as a median BSA of 7.0 (IQR 3.00–15.00) and 12.0 (IQR 5.00–22.50) ( P = 0.002), and median DLQI of 11.0 (6.00–15.00) and 21.0 (6.50–25.00) ( P = 0.007), respectively. Conclusions: Chilean patients had significantly more severe psoriasis compared with Brazilian patients in our study. While nonbiologic treatments for moderate-to-severe psoriasis were available in both LA countries, there is a high need for improvement in access to more effective psoriasis treatments including biologics. Our results highlight a significant gap between treatment recommendations in international psoriasis guidelines and real-world situations in Brazil and Chile.